Application of small and micro cogeneration units - Radosavljević, Milan R. (Vojnotehnički glasnik / Military Technical Courier, 2017)
By 1973, low oil prices had provided the production of relatively cheap electricity. A sudden increase in gas prices caused a need for developing energy technologies as well as a need for increasing the efficiency of power plants. At the same time, increased environmental awareness as well as the awareness of the growing scarcity of energy sources required greater attention to preserving the environment and the existing resources, so small and micro cogeneration plants become efficient and competitive energy producers. The United States and Canada are currently lagging behind Europe and Japan in relation to the development of micro cogeneration units, partly because of differences in heating systems, energy prices and political framework. In accordance with the Kyoto Protocol, Japan is obliged to reduce its global warming i.e. gas  emissions by 6% of the 1990 level. However, CO2 emissions continue to grow, which means that it is currently estimated that Japan must reduce emissions by 14% to meet the goal. Japan should promote all possible ways to effectively reduce CO2 emissions. In this regard, it continues to give support to micro cogeneration marketing, especially for models suitable for residential buildings. It is estimated that, in the next few years, energy production by cogeneration will reach 75% of the total production at the European level. In Italy, ecological energy makes 30% of the total consumption, in the Netherlands 33%, and in Denmark and the UK it is almost completely present.
Keywords: micro cogeneration; small cogeneration